2020
DOI: 10.1016/j.neuron.2019.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Evoked Synaptic Regulation in the Nucleus Accumbens Requires Astrocyte Activity

Abstract: Dopamine is a key neurotransmitter involved in physiological processes, such as learning and memory, motor control and reward, as well as, pathological conditions, such as Parkinson's disease and drug abuse. In contrast to the extensive studies on neurons, the role of astrocytes in dopaminergic signaling remains largely unknown. Using transgenic mice, optogenetics and pharmacogenetics, we studied the role of astrocytes on the dopaminergic system. We show that in freely-behaving mice, astrocytes in the nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
185
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 68 publications
21
185
3
Order By: Relevance
“…Multiple signaling pathways may be putatively involved in the bidirectional astrocyte-neuron communication underlying the observed results. On the one hand, astrocytes are known to respond with Ca 2+ elevations to a wide variety of neurotransmitters released at cortical synapses active during the sensory stimulation, including glutamate, GABA, acetylcholine, norepinephrine or dopamine 9 , 11 , 42 , 43 . On the other hand, multiple astrocyte signaling mechanisms may influence neuronal activity 9 , 11 , 44 , either through synapse-specific or volume transmission 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling pathways may be putatively involved in the bidirectional astrocyte-neuron communication underlying the observed results. On the one hand, astrocytes are known to respond with Ca 2+ elevations to a wide variety of neurotransmitters released at cortical synapses active during the sensory stimulation, including glutamate, GABA, acetylcholine, norepinephrine or dopamine 9 , 11 , 42 , 43 . On the other hand, multiple astrocyte signaling mechanisms may influence neuronal activity 9 , 11 , 44 , either through synapse-specific or volume transmission 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences highlight important roles of astroglia in regulating neural activity, brain states, and animal behavior, both in vertebrates (Brancaccio, Patton, Chesham, Maywood, & Hastings, 2017) and invertebrates (Ma, Stork, Bergles, & Freeman, 2016). Studies in rodents showed that astroglial cells are highly dynamic components of the brain, which respond to locomotion (Nimmerjahn, Mukamel, & Schnitzer, 2009; Sekiguchi et al, 2016; Slezak et al, 2019) or sensory stimulation (Gu et al, 2018; Slezak et al, 2019) with prominent changes in astroglial calcium levels and can regulate learning (Adamsky et al, 2018; Corkrum et al, 2020) or other state transitions (Bojarskaite et al, 2019; Cui et al, 2018; Oe et al, 2020; Poskanzer & Yuste, 2016) in the brain. Norepinephrine (Bekar, He, & Nedergaard, 2008; Oe et al, 2020; Salm & McCarthy, 1990; Shao & McCarthy, 1997) and acetylcholine (Araque, Martin, Perea, Arellano, & Buno, 2002; Pabst et al, 2016; Takata et al, 2011) are proposed to be the primary triggers for activating astroglia, yet several other molecules including glutamate (Hamilton et al, 2008; Mothet et al, 2005; Sun et al, 2013) play prominent roles in astroglial physiology.…”
Section: The Role Of Astroglia In Neural Circuit Function and Animalmentioning
confidence: 99%
“…Such regulatory mechanism is functionally important because it contributes to the modulation of both excitatory synaptic transmission and acute hyperlocomotor effects of d-amphetamine. 52 Although D1Rs expressed in BGCs do not participate to the regulation of GluA1 phosphorylation, their potential role in the regulation of BGCs Ca 2+ signaling will require further investigation.…”
Section: D-amphetamine-induced Increase Of Ps845-glua1 Requires Normentioning
confidence: 99%